2015
DOI: 10.1016/j.energy.2015.01.104
|View full text |Cite
|
Sign up to set email alerts
|

A probabilistic approach to solve the economic dispatch problem with intermittent renewable energy sources

Abstract: a b s t r a c tIn this paper, a methodology for solving the ED (economic dispatch) problem considering the uncertainty of wind power generation and generators reliability is presented. The corresponding PDF (probability distribution function) of available wind power generation is discretized and introduced in the optimization problem in order to probabilistically describe the power generation of each thermal unit, wind power curtailment, ENS (energy not supplied), excess of power generation, and total generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(20 citation statements)
references
References 33 publications
0
19
0
1
Order By: Relevance
“…One of these metrics is the similarity ratio, which is the ratio of average intra-cluster to average inter-cluster distances, in the space of moments. These are given by equations (24) and (25), respectively. The average intra-cluster distance measures the compactness of clusters; whereas, the average inter-cluster distance measures the cluster discrimination.…”
Section: Clustering Results For Overloading Snapshotsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of these metrics is the similarity ratio, which is the ratio of average intra-cluster to average inter-cluster distances, in the space of moments. These are given by equations (24) and (25), respectively. The average intra-cluster distance measures the compactness of clusters; whereas, the average inter-cluster distance measures the cluster discrimination.…”
Section: Clustering Results For Overloading Snapshotsmentioning
confidence: 99%
“…The authors in Ref. [24] develop an analytical methodology to consider uncertainty in wind power generation and generator availability. Their methodology is compared with MCS, and it is reported that the results obtained using both approaches largely coincide.…”
Section: State-of-the-art Literature Review On Operational Uncertaintmentioning
confidence: 99%
“…Note that for the Hybrid Basic Events of the inverters, variable failure rates are updated during the simulation of an iteration in order to consider the variation of the aging variable. From lines (4)(5)(6)(7)(8)(9)(10)(11), the other variables required for the Monte Carlo simulation are initialized and line (12) sets the name of the Simulink model (which corresponds with the .slx file) that will be called at the beginning of the simulation (in our code it is named 'hybrid_pair_1'). With line (13) the variables initialized with the Matlab script are passed to the Simulink environment and line (14) starts the simulation.…”
Section: Simulation Of the Shyfta Modelmentioning
confidence: 99%
“…The greatest issue to face is linked with the intermittent nature of the renewable resources, which affect the stability of the electrical power grid, unable to manage the power fluctuations of renewable power plants production and the difficulties with energy storage [5].…”
Section: Introductionmentioning
confidence: 99%
“…Numerical weather prediction (NWP)-based multiple temporal and spatial scales solar PV power forecasting is a good measure to facilitate more economic decisions for the dispatch operation of power system. With this knowledge, the solar PV generation can be added into the grid operation more precisely like the economic dispatch considering the uncertainty of deep penetration of wind power, which will make it possible to schedule and adjust the dispatchable generators' output to coordinate the fluctuation of solar PV plants as well as the wind farms and the electricity load from users' demand [10].…”
Section: Introductionmentioning
confidence: 99%